Autogenic electrolysis of water powered by solar and mechanical energy. (January 2022) - Hu, Ya; Chen, Libo; Chai, Zhigang; Zhu, Jiefang; Wang, Zhong Lin; Zhang, Shi-Li; Zhang, Zhi-Bin
Abstract: A dual-bandgap photoelectrochemical (PEC) cell with two semiconductors stacked in tandem is a widely adopted concept to capture a large fraction of the solar spectrum for water splitting. While two photons are theoretically needed to produce one H2 molecule using single-bandgap PEC cells, four photons are generally required for one H2 molecule in the dual-bandgap cells because of an unavoidable charge recombination at the solid-solid interface. Here, triboelectric effects are exploited in the form of triboelectric nanogenerator (TENG) to allow for the generation of one H2 molecule at the expenses of two photons in a dual-bandgap device using an array of core/shell p -type silicon/anatase-TiO2 nanowires as photoelectrode. The TENG, that converts mechanical energy to electricity, efficiently suppresses the charge recombination at the interface and significantly increases the energy of the photo-generated carriers required for the simultaneous water reduction and oxidation. The synergy of photoexcitation and triboelectrics results in a rate of hydrogen production in a neutral Na2 SO4 electrolyte around 150 times higher than that of the counterpart, i.e., the device in the absence of TENG. Furthermore, the TENG-induced enhancement in the PEC water splitting remains substantial even when the solar power density is reduced to 20 mW/cm 2 . Graphical Abstract: ga1 Highlights: An autogenic hybrid water splitter comprising a dual-band-gap photoelectrode and triboelectric nanogenerator was reported. The hybrid water splitter produced one hydrogen molecule in expense of two photons, rather than four photons. The water splitter produced around 10 microliter hydrogen per minute per centimetre square in a neutral electrolyte. The hybrid water splitter performed equally well at weaker solar illumination with the solar power density at 20 mW/cm 2 .